2019
DOI: 10.2196/13203
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health Interventions by Social Robots: Systematic Review of Randomized Controlled Trials

Abstract: Background Social robots that can communicate and interact with people offer exciting opportunities for improved health care access and outcomes. However, evidence from randomized controlled trials (RCTs) on health or well-being outcomes has not yet been clearly synthesized across all health domains where social robots have been tested. Objective This study aimed to undertake a systematic review examining current evidence from RCTs on the effects of psychosocial interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(56 citation statements)
references
References 79 publications
2
46
0
Order By: Relevance
“…Although the development of robotics may raise some ethical issues [ 36 ], none of the students participating in our study showed any ethical concerns about who could decide to turn off the robot or set it up, similar to the results in other studies [ 31 ]. The surveyed students believed that older people should not be able to turn off the robot completely for their safety.…”
Section: Discussionsupporting
confidence: 86%
“…Although the development of robotics may raise some ethical issues [ 36 ], none of the students participating in our study showed any ethical concerns about who could decide to turn off the robot or set it up, similar to the results in other studies [ 31 ]. The surveyed students believed that older people should not be able to turn off the robot completely for their safety.…”
Section: Discussionsupporting
confidence: 86%
“…For example, ''Pet robot intervention for people with dementia: a systematic review and meta-analysis of randomized controlled trails'' [8], examined behavioral and psychological symptoms of dementia (BPSD). ''Psychosocial Health Interventions by Social Robots: Systematic Review of Randomized Controlled Trials'' [73] generalized from interventions with children, people with autism and older adults. Finally, the systematic review ''Robotics to Enable Older Adults to Remain Living at Home'' [74] was excluded due to methodological weakness identified by its researchers.…”
Section: B Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…A few studies have shown further benefits, providing encouraging results in contrast to the hypothesis that robotic devices only focus on an emotional level, but can be used significantly as cognitive stimulators, optimizing both seniors' interactivity and processing ability [35,43]. Results from robotic psychological interventions are usually described in terms of better or improved older adults related outcomes, like more efficient cognitive or neural functioning, improved anxiety coping abilities, or better quality of life [44].…”
Section: Robotsmentioning
confidence: 99%
“…However, one limitation of some studies included in this scoping review, especially those dealing with older adults with dementia or mild cognitive impairment is that those observed positive outcomes often imply less decline, rather than real positive improvements [44][45][46].…”
Section: Robotsmentioning
confidence: 99%